DIY Low-Budget Smartphone Photometer - Olaf Elsholz and Tereza Christina Rodrigues Elsholz and Ulrich Scheffler (G.I.T. Laboratory Journal, 2018)
A LED photo sensor, designed as a kit and assembled more than 100 times by school groups, has been fundamentally revised. In the new version, the light detector is now a component of digital electronics and is connected to a Wifi- (WLAN-) enabled microprocessor, which transmits its data to a smartphone. At approx. 30 €, the price of the required components is quite moderate, and instead of the previously required multimeter, now any commercially available smartphone can be used.